Catholic shrines in Chennai, India: the politics of renewal and apostolic legacy - Nagy, Thomas Charles (Routledge, Taylor & Francis Group, 2017)
Brief history of Indian Christianity as it pertains to the politics of modern-day Catholic renewal in Chennai, Tamil Nadu the nature and location of value -- Reviving the history of St. Thomas: martyrdom and burial as a new myth of origin for Indian Catholics in Chennai -- The influences of Indian political ideologies on Catholic revivalist strategies in Chennai -- The physical renovation of San Thome Cathedral: revival through tourism, branding, and heritage preservation -- A broader view of Catholic renewal in Chennai: a strategy for shrinal-based evangelization -- Conclusion on Catholic renewal in Chennai